Islamic Senior High School Students' Attitude toward Literature in English; A Descriptive Study at MAN 1 Kota Bukittinggi - Kharisma Khairunnisaa; Delvi Wahyuni (Universitas Negeri Padang, 2021)
Curriculum 2013 created some changes in the regulations and method used during the learning process. One of which is the existence of elective classes in Senior High School level, including English elective class. This class aimed to give the opportunity for the students to learn other subject outside their compulsory subjects based on their interest and passion. This regulation also existed in Islamic High School. There are more compulsory subjects in this school rather than in the regular school. Therefore, this study aimed to explore Islamic Senior High School students’ attitude toward literature in English. The participants of this research were 24 students of twelve-grade in science specialization class of MAN 1 Kota Bukittinggi. The sample was chosen using purposive sampling technique. The criterion for choosing the sample was the students who took English in elective class. This study employed descriptive research. The instrumentations of this research were questionnaire as the primarily and interview as the secondary to get deeper information. There were several categories asked to the students, which were students’ favorite genre of literature, advantages of literature, language preference in the classroom, and also the influence of numerous subjects in Islamic high school. Overall, the result of this research showed that students of Islamic Senior High School have positive attitude toward literature in English.